Analisis Bahasa Persuatif Wacana Komersial pada Iklan Perbankan - Maria Polencys Pere Ri’a (Program Studi Pendidika Bahasa dan Sastra Indonesia, 2020)
The study, entitled Analysis of Persuasive Language of Advertising Discourse on Banking Advertising, aims to identify and analyze the language elements in the structure of persuasive commercial advertising discourse. In this case there are several selected language elements which predominantly contribute to the persuasive function of language in commercial advertising. know and analyze the composition and cohesion of persuasive advertising discourse. The composition of commercial advertising discourse is a composition that has relevance to form a persuasive discourse, such as reasoning and its techniques. The research approach used is a qualitative descriptive approach. The data was collected descriptively through literature study and the data collected was selected according to predetermined criteria. Therefore, all data on commercial advertising discourse texts that match the criteria are defined as research data. The results of the study prove that the language structure with (1) themes that emphasize service trust, (2) intagible references because the products offered in the service company category are services, (3) the choice of words that stand out is the ones that are closely related to the type of product reference. which is offered.Based on the data analysis, the conclusion is related to the problem and the object of study is the structure of the language with (1) a theme that emphasizes the trust of the servant, the referent which is integible and the choice of words that stands out are the choice of words that are closely related to the type of product referent. Cohesion in advertising discourse is intended to create coherent meanings. The persuasive context on service company advertising discourse includes participants in the advertising discourse, the most prominent functions of language are expressive, connective and aesthetic functions.